(untitled) (Fiep Bulletin - online, 2014)
This work has for objective to present reflections on the directions/meanings of the culture of the movement, constructed in the lessons of Physical Education, in the College of Application of the UNIVALI. The work was developed in disciplines them of Supervised Period of training: Practical research of the Pedagogical and Practical Professor - Integrated Projects were pautou in the principles of the qualitative research, and the collection of data was become fullfilled by means of interview, participant comment, guided by daily of field and planned monitorias. The research occurred in the period of March the June of 2006 with the intention of problematizar the teaching action to identify problematic, a discutiz one it and to consider metodológicas alternatives. The experience of the monitorias made possible the joint practical theory, reflection of the context of the pertaining to school physical education and organization of the plan of action for the interventions. The analysis of the collected data contributed for the understanding of the paper of the professor as mediating in the process of constitution of sensible and meanings related to the corporal culture.